Vitamin D Status in Children in Greece and Its Relationship with Sunscreen Application - Gavriela Maria Feketea; Ioana Corina Bocsan; Georgios Tsiros; Panagiota Voila; Luminita Aurelia Stanciu; Mihnea Zdrenghea (MDPI AG, 2021)
The aim of this study was to characterize the prevalence and seasonal variation of vitamin D (vit D) deficiency/insufficiency in healthy children and adolescents in Greece, and to explore its relationship with the use of sunscreens. The serum level of 25-hydroxy-vitamin D (25(OH)D) was measured in 376 children and adolescents (184 males and 192 females) with a mean age of 7.6 ± 4.9 years, at different time points over a period of 13 months. The prevalence of low serum 25(OH)D level, including deficiency and insufficiency, was 66.2%. The lowest mean 25(OH)D was observed in the month of January (17.9 ± 6.8 ng/mL) and the highest in September, July, August, and October (34.6 ± 8.7, 33.0 ± 9.4, 30.1 ± 8.2, and 30.1 ± 10.6 ng/mL, respectively). Higher levels of serum 25(OH)D were detected in the children to whom sunscreens had been applied on the beach (p = 0.001) or off the beach (p < 0.001). The subjects with deficiency and insufficiency were significantly older than those with normal levels of 25(OH)D, but no significant differences were demonstrated according to gender. This study emphasizes the high prevalence of low serum levels of 25(OH)D and their seasonal variation in children living in a region characterized by many hours of sunshine. Our data suggest that the real-life use of sunscreens during the summer months allows sufficient sunlight to be received to enable production of vit D at a level adequate to maintain normal serum levels. Vit D supplements should be given to children during the months of lower sun exposure.